2023
DOI: 10.1021/acsabm.2c01054
|View full text |Cite
|
Sign up to set email alerts
|

Biosensors Based on Graphene Oxide Functionalized with Benzothiadiazole-Derived Ligands for the Detection of Cholesterol

Abstract: In this work, imidazole-or imidazolium-based benzothiadiazole ligands functionalized on graphene oxide combined with cholesterol oxidase constitute efficient, robust, and easy-to-handle materials with high biosensing activity for the detection of cholesterol by colorimetric methods. The presence of lanthanum(III) supported on graphene oxide as a possible coordinating site for the benzothiadiazole ligands was also evaluated, and its bioactivity was compared to that of the analogous material without the rare-ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Lanthanum doped-graphene oxide functionalized with imidazole-or imidazolium-based benzothiadiazole ligands were use as fluorescent biosensors to the detection of cholesterol by colorimetric procedures [68]; for the above task, ChOx (cholesteroloxidase) enzyme was immobilize onto the various materials. Results showed that not all the compositions performed equally, summarizing Table 12 the limiting detections yielded by some of these derivatives.…”
Section: Using Ionic Liquids and Rare Earth Elements In The Developme...mentioning
confidence: 99%
“…Lanthanum doped-graphene oxide functionalized with imidazole-or imidazolium-based benzothiadiazole ligands were use as fluorescent biosensors to the detection of cholesterol by colorimetric procedures [68]; for the above task, ChOx (cholesteroloxidase) enzyme was immobilize onto the various materials. Results showed that not all the compositions performed equally, summarizing Table 12 the limiting detections yielded by some of these derivatives.…”
Section: Using Ionic Liquids and Rare Earth Elements In The Developme...mentioning
confidence: 99%
“…In 2019, Liu and coworkers reported a pyrazole-BTD conjugate that was used for the detection of Cu( ii ) and hydroxide by fluorescence spectroscopy. 38,39 Recently, Scholten and coworkers reported that ionic BTD-imidazole derivatives were efficient biosensors for cholesterol detection 40 while Neto and coworkers described pyridine-BTD derivatives that were applied as plasma membrane fluorescent markers. 41 On the other hand, different BTD-amine derivatives have been developed for uses as semiconductors for solar cells, 42 red-fluorescent emitters, 43 and charge-transport emitters for OLED technology.…”
Section: Introductionmentioning
confidence: 99%